Introductory circuit analysis - Boylestad, Robert L. (Pearson, 2024)
Introductory Circuit Analysis has been the number one acclaimed text in the field for over 50 years. Boylestad presents complex subject matter clearly and with an eye on practical applications. He provides detailed guidance in using the TI 89 Titanium calculator, the choice for this text, to perform all the required math techniques. Challenging chapter-ending review questions help you deepen your grasp of the material. Updated with the most current, relevant content, the 14th Edition places greater emphasis on fundamentals and has been redesigned with a more modern, accessible layout. Topics requiring a solid understanding of Power Factor, Lead and Lag concepts have been significantly enhanced throughout the text.